Desain Pedoman Implementasi Sistem Pengendalian Intern Pemerintah di Lingkungan Perguruan Tinggi Negeri - Imam Mulyono; Didik Purwantoro (Pusat P2M Politeknik Negeri Batam, 2019)
The Purpose of this research to evaluate and design guidelines implementation internal goverment control system in State Polytechnic of Malang. Kind of this research was descriptive using qualitative apporoach and the data that were used in this study were primer data colleted from interview result with internal audit unit at State Polytechnic of Malang. The result of this research indicate State Polytechnic of Malang don’t have guidelines implementation internal goverment control system. Researcher recommended guidelines implementation internal goverment control system design at State Polytechnic of Malang for fulfill indicators: infrastructure needed to build, the implementation, and the legal basis. Advice for directure of State Polyechnic of Malang immediately communicate to all academic community so they can understand about guidelines implementation internal goverment control system.